Vaunting the independent amateur: Scientific American and the representation of lay scientists. - Johnston, Sean F. (Annals of Science, 2018)
This paper traces how media representations encouraged enthusiasts, youth and skilled volunteers to participate actively in science and technology during the twentieth century. It assesses how distinctive discourses about scientific amateurs positioned them with respect to professionals in shifting political and cultural environments. In particular, the account assesses the seminal role of a periodical, Scientific American magazine, in shaping and championing an enduring vision of autonomous scientific enthusiasms. Between the 1920s and 1970s, editors Albert G. Ingalls and Clair L. Stong shepherded generations of adult ‘amateur scientists’. Their columns and books popularized a vision of independent non-professional research that celebrated the frugal ingenuity and skills of inveterate tinkerers. Some of these attributes have found more recent expression in present-day ‘maker culture’. The topic consequently is relevant to the historiography of scientific practice, science popularization and science education. Its focus on independent non-professionals highlights political dimensions of agency and autonomy that have often been implicit for such historical (and contemporary) actors. The paper argues that the Scientific American template of adult scientific amateurism contrasted with other representations: those promoted by earlier periodicals and by a science education organization, Science Service, and by the national demands for recruiting scientific labour during and after the Second World War. The evidence indicates that advocates of the alternative models had distinctive goals and adapted their narrative tactics to reach their intended audiences, which typically were conceived as young persons requiring instruction or mentoring. By contrast, the monthly Scientific American columns established a long-lived and stable image of the independent lay scientist.